THE STAGING OF BREAST CANCER DIAGNOSED IN SÃO CARLOS PUBLIC HEALTH SYSTEM - Macchetti, Alexandre Henrique (Medicina (Ribeirao Preto), 2007)
Introduction: data on breast cancer stage at diagnosis are easily available for most developed countries while they are more difficult to obtain for countries of Latin America. Data of Instituto Nacional do Câncer reffer to 60% of breast cancer cases in late stage, however the present of Mastology Service of Heath Secretary of São Carlos showed different data that estimulate the evaluation of the breast cancer stage and age at diagnosis in the patients of public health system resident at São Carlos and comparation to statistics of others institutions.Patients and Methods: records of 106 women newly diagnosed with breast cancer between March 2000 and December 2004 at Mastology Service of Health Secretary of São Carlos (SUS) were reviewed. The breast cancer stage and age at diagnosis were annotade. Breast cancer stage was grouped according to TNM (AJCC) and SEER Summary Staging systems, and age at diagnosis was grouped according age under or above the median of the group of patients to correlate with the breast cancer stage. Results: In the TNM staging system the tumors in situ corresponded to 6,6% of all cases, tumors at stage I to 25,4%, stage II to 44,3%, stage III to 17,0 % and stage IV to 6,6%. In the SEER staging system the tumors in situ corresponded to 6,6% of all cases, local tumors to 62,2%, regional tumors to 24,5% and diseminated tumors to 6,6%. There were more early stage cases while using TNM (76,3%) than while using SEER staging system (68,8%). There was association of age group under 56 years with early breast cancer stage at diagnosis in AJCC staging system, but not in SEER staging system. Conclusion: relevant data to a better understanding of the breast cancer care are presented, permiting improve community-level interventions to cancer detection, and also a data-driven rationale for allocating resources to cancer-related policies, programs, and services.